2015
DOI: 10.1097/scs.0000000000002021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Presurgical Positioning on Skull Shape in Sagittal Suture Synostosis

Abstract: Before surgery, positioning patients with sagittal suture synostosis on the back of the head is a feasible and effective way of changing head shape. More research is needed to evaluate the postsurgical effects on the long term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In our experience, manuscripts that paired helmet therapy with surgical intervention did not demonstrate any long-term, significant differences in the postoperative CI or cephalic morphology attributable to orthotics. 20,43,50,54,59 The findings reiterate that the use of a helmet is not mandatory. In addition, major questions about its benefit remain unresolved.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In our experience, manuscripts that paired helmet therapy with surgical intervention did not demonstrate any long-term, significant differences in the postoperative CI or cephalic morphology attributable to orthotics. 20,43,50,54,59 The findings reiterate that the use of a helmet is not mandatory. In addition, major questions about its benefit remain unresolved.…”
Section: Discussionmentioning
confidence: 83%
“…Helmet therapy and presurgical skull positioning have been discussed in several manuscripts as an adjacent treatment to surgery. While van Veleen et al 59 reported changes in preoperative head circumference after undergoing nonrestrictive skull positioning therapy, these results have not been correlated with postoperative outcomes. Helmet treatment was almost exclusively seen in the cohort 0 to 6 months of age (16 of 17 total articles) and in all but one study involving MIS techniques.…”
Section: Discussionmentioning
confidence: 95%